(untitled) (Bangladesh Journal of Pharmacology, 2015)
The study was devised to investigate the effect of retinoic acid trifloromethyl chalcone (RAFC) on mammary carcinogenesis in female rats. The data revealed a significant decrease in number of rats with mammary tumor, number of tumors per rat and tumor volume by 54, 72 and 75% respectively in RAFC group compared to control group. The ibuprofen treated rats also showed a significant decrease in number of rats with tumor, number of tumors per rat and tumor volumes by 43%, 55%, and 59%, respectively. Treatment of rats with RAFC also increased the latency period of tumor induction significantly. Median detection period (50% of tumors) was 92, 83 and 56 days respectively in the rats from RAFC, ibuprofen and control groups respectively after DMBA induction. These results demonstrate that RAFC possesses strong chemopreventive activity against mammary carcinogenesis.